2008
DOI: 10.1177/8756479308323128
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Triphasic, Biphasic, and Monophasic Doppler Waveforms

Abstract: Doppler waveform analysis is a fundamental part of evaluating peripheral arterial disease. Waveform characteristics are traditionally defined as multiphasic (triphasic, biphasic) and monophasic. The purpose of this investigation is to evaluate whether sonography professionals correctly classify waveforms into these three categories. Thirty Doppler waveforms (15 continuous-wave [CW] and 15 pulsed-wave [PW] Doppler) were obtained from patients with previous noninvasive peripheral arterial evaluations. Participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 3 publications
2
41
0
Order By: Relevance
“…According to this approach, the flow pattern is described as "biphasic" if two sounds are heard during each cycle and as "triphasic" if three sounds are heard. More recently, sonologists have held that phase is defined in terms of discrete flow components in either direction (ie, portions on either side of the baseline) (8,11). This definition is based on observations of the spectral Doppler waveform.…”
Section: Flow Directionmentioning
confidence: 99%
“…According to this approach, the flow pattern is described as "biphasic" if two sounds are heard during each cycle and as "triphasic" if three sounds are heard. More recently, sonologists have held that phase is defined in terms of discrete flow components in either direction (ie, portions on either side of the baseline) (8,11). This definition is based on observations of the spectral Doppler waveform.…”
Section: Flow Directionmentioning
confidence: 99%
“…Given the signifi cant variability in classifying arterial Doppler waveforms morphologies recorded using the Doppler technique [10], attention should be paid to the teaching methods. No specifi c teaching method has been proposed or validated for Doppler signals, even though analysis of the latter is a key element in vascular practice.…”
Section: Teaching Methodsmentioning
confidence: 99%
“…Regarding ABI, a certain number of measurements must be recorded to build up competence [6,39,40]. Studies conducted by Scissons highlight a better system for classifying Doppler waveform morphologies with the person gaining experience with every waveform analysis [8,10]. Studies should be carried out to establish the best way of teaching arterial waveform analysis and to improve practices for better patient management.…”
Section: Teaching Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is observed that the transition from normal to abnormal is not always clear cut and the biphasic waveforms are associated with the most confusion and variability in their recognition by health care professionals. 48 Figure 1 is a simple illustration of the correlation between Doppler ultrasound waveforms, ABPIs, and the extent of occlusion. 49 Duplex ultrasound scanning.…”
Section: Noninvasive Vascular Assessment (Niva)mentioning
confidence: 99%